Determinants of premarital sexual initiation among Wukro high school and preparatory students, Eastern Tigray, Northern Ethiopia - Gebeye, Ejigu; Azale, Telake; Alemu, Kassahun (Ethiopian Journal of Reproductive Health, 2018)
Abstract Background: Sexual activities among adolescents have been increasing worldwide. The risky, unprotected and non-voluntary nature of sexual activities of adolescents put them at higher reproductive health problems including HIV/AIDS. Objective: The aim of the study was to determine premarital sexual initiation and identify associated risk factors among Wukro preparatory and high school students, Eastern Tigray. Methods: Institution based cross sectional survey was conducted on April 30, 2010. Data were collected from 588 students using pretested, structured and self administered questionnaire selected by stratified cluster sampling method. Data were entered, cleaned and analyzed using SPSS version 16.0. Logistic regression model was used to identify predictors of premarital sexual initiation and to control confounders. Results: Three hundred ten (52.7%) males and 278(47.3%) females participated in the study. A quarter, 152(25.9%) of the participants had premarital sexual debut. Among them, 86 (56.57%) had used condom at the first sexual debut. Total correct and consistent condom use was reported in 50(58.1%) of the sexually active students who had used condom at the first sexual initiation. Age less than 18 years was protective factor for premarital sexual debut [AOR at 95%CI: 0.42(0.21, 0.86)]. However, substance abuse like alcohol consumption and cigarette smoking as well as peer pressure were risk factors for premarital sexual initiation. Conclusion: Both premarital and early sexual initiation was high but total correct and consistent condom utilization was low in relative terms. The need to strengthen age and gender based IEC/BCC services about reproductive health issues within the school environment has paramount importance (Ethiopian Journal of Reproductive Health , 2012,6(1): 64-69).